Effect of abdominal girth, vertebral column length, and hip/shoulder width ratio on the spread of spinal anesthesia in term parturients undergoing elective cesarean section: A prospective observational non-randomized study - Anil K Bhiwal; Heena A Bhatt; Lalita Jeengar; Karuna Sharma; Aditi S Baghel; Sunanda Gupta (Wolters Kluwer Medknow Publications, 2022)
Background: Spinal anesthesia is the preferred technique for cesarean section, and a suitable level of spinal anesthesia is essential, which may be variable in every parturient. The aim of this study was to evaluate the correlation of abdominal circumference (AC), vertebral column length (VCL), hip shoulder width ratio (HSR), and vertebral column length (VCL)/Abdominal Circumference (AC)2 with the spread of spinal anesthesia in term parturient undergoing elective cesarean section. Methods: Two hundred term parturients undergoing elective cesarean section were enrolled in this prospective observational study. Spinal anesthesia was performed with 10 mg (2 ml) of 0.5% hyperbaric bupivacaine in L2-L3 or L3-L4 interspace using a 25 G Quincke needle. The cephalad spread (loss of pinprick discrimination) was assessed up to 30 minutes after intrathecal injection. Linear regression analysis was used to analyze the relationship between age, weight, height, body mass index (BMI), AC, VCL (C7-Sacral hiatus and C7-iliac crest), HSR, VCL/AC2, and the spread of spinal anesthesia. Results: The maximum sensory level showed a significant correlation with AC (P < 0.001), VCL [C7-SH and C7-IC] (P < 0.039 and P < 0.025) and VCL/AC2 (P < 0.001). Individually, hip width and shoulder width showed a significant correlation with cephalad spread of spinal anesthesia (P < 0.05); however, HSR had no significant correlation with the spread of anesthesia (P > 0.05). Conclusion: AC, VCL, and VCL/AC2 have a significant correlation with cephalad spread of spinal anesthesia when a fixed dose of hyperbaric bupivacaine is used in term parturients undergoing elective cesarean section, while HSR did not show any significant correlation.